Aging-Related Decline of Autophagy in Patients with Atrial Fibrillation-A Post Hoc Analysis of the ATHERO-AF Study - Francesco Versaci; Valentina Valenti; Maurizio Forte; Vittoria Cammisotto; Cristina Nocella; Simona Bartimoccia; Leonardo Schirone; Sonia Schiavon; Daniele Vecchio; Luca D'Ambrosio; Giulia Spinosa; Alessandra D'Amico; et al. (MDPI AG, 2022)
Background: Aging is an independent risk factor for cardiovascular diseases. The autophagy process may play a role in delaying aging and improving cardiovascular function in aging. Data regarding autophagy in atrial fibrillation (AF) patients are lacking. Methods: A post hoc analysis of the prospective ATHERO-AF cohort study, including 150 AF patients and 150 sex- and age-matched control subjects (CS), was performed. For the analysis, the population was divided into three age groups: <50-60, 61-70, and >70 years. Oxidative stress (Nox2 activity and hydrogen peroxide, H2O2), platelet activation (PA) by sP-selectin and CD40L, endothelial dysfunction (nitric oxide, NO), and autophagy parameters (P62 and ATG5 levels) were assessed. Results: Nox2 activity and H2O2 production were higher in the AF patients than in the CS; conversely, antioxidant capacity was decreased in the AF patients compared to the CS, as was NO production. Moreover, sP-selectin and CD40L were higher in the AF patients than in the CS. The autophagy process was also significantly impaired in the AF patients. We found a significant difference in oxidative stress, PA, NO production, and autophagy across the age groups. Autophagy markers correlated with oxidative stress, PA, and endothelial dysfunction in both groups. Conclusions: This study provides evidence that the autophagy process may represent a mechanism for increased cardiovascular risk in the AF population.